KONTEKTUALISASI MAKNA ‘TAHLUKAH’ DALAM MITIGASI BENCANA - irfan afandi (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2023)
Disaster mitigation, in today's era, is very important to pay attention to; But most humans neglect to mitigate disasters. The Qur'anic concept of Tahlukah in Qs. al-Baqoroh:195 is important as a theological legitimacy of disaster mitigation. Of course, linking disaster mitigation with the meaning of the word tahlukah requires a contextual approach. The word means things that cause damage. Allah Almighty forbids man to plunge himself into tahlukah. How? The verse explains that man is commanded to spend (infaq) some of his property to minimize damage to the earth. The contextualization is that humans must be willing to invest in their environment. Investment in order to protect the environment can keep humans away from disasters caused by environmental damage. In addition, Allah Almighty is also commanded to ihsan; The contextualization is by maintaining the sustaansibility of investments that have been infused to protect the environment. Waste until the investment that has been spent is not maintained as well as possible. In the context of tarbawi interpretation, environmental infaq or investment in protecting the environment must be conveyed massively to the community. This discourse is not only conveyed in the community but must also be introduced early in madrassas / schools. Thus, the command to abstain from tahlukah can be a useful knowledge in the future. This article has limitations about the idea of environmental infaq that have not been studied in depth due to the concentration of writing on the concept of tahlukah. The hope is that there are researchers who study this.